2020
DOI: 10.1109/access.2020.3012292
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of White Blood Cancer From Bone Marrow Microscopic Images Using Convolutional Neural Networks

Abstract: Leukocytes, produced in the bone marrow, make up around one percent of all blood cells. Uncontrolled growth of these white blood cells leads to the birth of blood cancer. Out of the three different types of cancers, the proposed study provides a robust mechanism for the classification of Acute Lymphoblastic Leukemia (ALL) and Multiple Myeloma (MM) using the SN-AM dataset. Acute lymphoblastic leukemia (ALL) is a type of cancer where the bone marrow forms too many lymphocytes. On the other hand, Multiple myeloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…In medical science, the study of characteristics and mechanisms of cell functions, identifying external damaging factors, and finding methods to prevent and treat cellular disorder diseases in the human body requires the preparation of cell samples with suitable purity. Blood is the most important component of the human body, containing various types of essential cells, including red blood cells (RBCs), white blood cells (WBCs), and platelets which are produced in the bone marrow and released into the bloodstream [ 1 ]. WBCs comprise about 1% of whole blood and have a significant role in the body’s immune system.…”
Section: Introductionmentioning
confidence: 99%
“…In medical science, the study of characteristics and mechanisms of cell functions, identifying external damaging factors, and finding methods to prevent and treat cellular disorder diseases in the human body requires the preparation of cell samples with suitable purity. Blood is the most important component of the human body, containing various types of essential cells, including red blood cells (RBCs), white blood cells (WBCs), and platelets which are produced in the bone marrow and released into the bloodstream [ 1 ]. WBCs comprise about 1% of whole blood and have a significant role in the body’s immune system.…”
Section: Introductionmentioning
confidence: 99%
“…In the medical domain, automated disease classification plays an important role during the mass data assessment and a perfectly tuned disease classification system further reduces the diagnostic burden of physicians and acts as an assisting system during the decision-making process [ 32 , 33 , 34 , 35 ]. Therefore, a considerable number of disease detection systems assisted by DL are proposed and implemented in the literature [ 36 , 37 , 38 , 39 , 40 ]. Recent DL schemes implemented in the LIDC-IDRI with fused deep and HCF helped achieve a classification accuracy of >97% [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…An integrated system was proposed where visual descriptors were used to measure the distance between the people and the methodology was able to achieve an accuracy of 93.3% [37]. Another deep learning solution was proposed that alerts the person as soon as they violate the social distancing norms via CCTV and PoseNet [38,39]. The research concluded that using a hybrid deep transfer learning model based on ResNet-50 and machine learning algorithms such as SVM, decision trees, etc.…”
Section: Related Workmentioning
confidence: 99%